Acquisitions by family businesses in continental Europe and their differences compared to private equity investors. (15th March 2019) - Schüler, Philipp; Mietzner, Mark; Schiereck, Dirk
This study explores whether family business investors and private equity investors in continental Europe significantly differ from their investment approach and performance. Therefore, we analyse 126 acquisitions of listed Continental European firms by family business investors or private equity firms from the years 2002 to 2012. Although most of the performance differences between both investor groups are not statistically significant, the results fit with the existing evidence on shareholder activism of institutional investors like private equity funds and corporate raiders. However, there are some significant differences with respect to target firm characteristics. Consequently, we suggest to increasingly consider family business investors in the research on shareholder activism in Continental Europe.